PENGUATAN KOMPETENSI GURU DALAM MERANCANG PEMBELAJARAN KONTEKSTUAL BERBASIS KEARIFAN LOKAL DI SMA NEGERI 3 LAHAT - Misdalina; Destiniar; Nyiayu Fahriza Fuadiah; Dina Octaria; Anggria Septiani Mulbasari; Marhamah; Tika Dwi Nopriyanti (Jurnal Berdaya Mandiri, 2026)
This community service program was motivated by the need to strengthen teachers’ competence in designing contextual learning that is relevant to students’ everyday lives. The program aimed to enhance teachers’ understanding and skills in developing teaching materials based on the local wisdom of Lahat Regency. It was conducted at SMA Negeri 3 Lahat through training and mentoring activities involving teachers as participants. The program consisted of several stages, including material presentation, discussion, identification of local wisdom potentials, development of teaching materials, presentations of participants’work, reflection, and completion of a satisfaction questionnaire. Data were collected through observation, participants’ teaching material products, and questionnaire responses. The results showed that the teachers gained a better understanding of the importance of integrating local wisdom into classroom learning. In addition, participants were able to develop teaching materials that connected subject content with the local context of Lahat Regency. The participants’ responses also indicated positive perceptions of the program’s usefulness, implementation, and potential application in schools. Therefore, this program contributed to strengthening teachers’ pedagogical competence in designing contextual learning based on local wisdom. Keywords: teacher competence; contextual learning; local wisdom; teaching materials